Sistem Pendukung Keputusan Penilaiaan Kinerja Auditor Terbaik Menggunakan Metode Multi Attribute Utility Theory (MAUT) Dan Pembobotan Rank Order Centroid (ROC) - Syahputri Lubis, Dwi Widiarti (Bulletin of Data Science, 2024)
Auditors are parties who play an important role for company management in decision making. Auditors are expected to be able to produce quality audits for management's needs in the decision-making process. This will help PT. Barindo Abadi Semesta in improving company performance through the auditor performance results obtained. One effort to get quality auditors is to carry out performance assessments and give awards to auditors for the performance and achievements they have made while working as auditors. One of the methods used is the Multi Attribute Utility Theory (MAUT) method using Rank Order Centroid (ROC) weighting. Based on the results of calculating the final value using the Multi Attribute Utility Theory (MAUT) method, there is an alternative choice, namely A2 as the best alternative choice with a final value of 0.847.